Extending the Community of Inquiry Framework: Development and Validation of Technology Sub-Dimensions - Şen-Akbulut, Mutlu; Umutlu, Duygu; Arıkan, Serkan (International Review of Research in Open and Distributed Learning, 2022)
Since the mandatory switch to online education due to the COVID-19 outbreak in 2020, technology has gained more importance for online teaching and learning environments. The Community of Inquiry (CoI) is one of the validated frameworks widely used to examine online learning. In this paper, we offer an extension to the CoI framework and survey, arguing that meaningful and appropriate use of technologies has become a requirement in today’s pandemic and post-pandemic educational contexts. With this goal, we propose adding three technology-related sub-dimensions that would fall under each main presence of the CoI framework: (a) technology for teaching, (b) technology for interaction, and (c) technology for learning. Based on exploratory and confirmatory factor analyses, we added 5 items for technology for teaching sub-dimension, 4 items for technology for interaction sub-dimension, and 5 items for technology for learning sub-dimension in the original CoI survey. Further research and practice implications are also discussed in this paper.